An Archival Examination of Gender-Specific Terminology in Public and Private Sector Collective Bargaining Agreements - Hillstead, Coy (Advances in Social Sciences Research Journal, 2023)
Organizations and labor unions are at the crossroads of transformational change in workplace demographics. In increasing numbers, female workers are entering fields and occupations that have historically been primarily occupied by male workers. However, despite these shifts in workplace demographics, many collective bargaining agreements (CBA’s) are outdated with the use of gender-specific terminologies which are rooted in the historic industrial workplace and contain terminology implicating a workplace and occupation only held by male workers. This article examined the frequency with which such gender-specific terminology is used in both public and private sector CBA’s. Additionally, the article also offers recommendations for both organizations and labor unions with respect to terminology changes in their CBAs. Failure to adapt and modify such language may reflect a lack of inclusion by both organizations and labor unions with respect to their employees and members.